The Effect of Government Ownership, Foreign Ownership, Managerial Ownership, Institutional Ownership on Financial Performance With Corporate Governance as Moderate in Soe Companies - Fibriani, Cut Dara; Islahuddin, Islahuddin; Zuraida, Zuraida (Riviera Publishing, 2022)
Introduction: This study examines the effect of government ownership, foreign ownership, managerial ownership, and institutional ownership on Financial Performance with Corporate Governance as moderating BUMN companies Post Privatization in 2015-2019. In this study, the data used is panel data. Panel data is a combination of time series and cross-section. Methods: The data analysis method used is multiple linear regression using the SPSS Version 26 application, in accordance with the research objectives, the type of research used in this study is hypothesis testing research. This research is causal. Results: The results show that Government Ownership, Foreign Ownership, Managerial Ownership, and Institutional Ownership affect Financial Performance. Conclusion: The size of the board of commissioners has no impact on financial performance. The size of the board of commissioners moderates the predictor of the effect of government ownership on economic performance because the size of the board of commissioners has no impact on financial performance (p?0.05). The size of the Board of Commissioners moderates the predictor of the influence of Foreign Ownership on Financial Performance because the size of the board of commissioners does not affect financial performance. The size of the board of commissioners moderates the effect of managerial ownership on economic performance because the size of the board of commissioners has no impact on financial performance, and the size of the board of commissioners moderates the effect of institutional ownership on economic performance because the size of the board of commissioners has no impact on financial performance (p>0.05).